2018
DOI: 10.1038/s41598-018-30218-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between transoral laser surgery and radiotherapy in the treatment of early glottic cancer: A systematic review and meta-analysis

Abstract: A therapeutic decision in the treatment of Tis/T1a glottic carcinoma with radiotherapy (RT) or transoral laser surgery (TOS) is still an open issue. Oncologic outcome and voice quality may support the choice for the latter To conduct a systematic review and meta-analysis to compare oncologic and functional outcomes of TOS and RT as treatment options for Tis/T1a glottic cancer. Literature research on online databases was carried out. Potentially eligible articles were reviewed. Relevant articles were selected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 26 publications
(32 reference statements)
3
54
0
4
Order By: Relevance
“…This is consistent with previous studies. A recent meta‐analysis by Guimaraes et al of eight studies with over 1000 patients with Tis and T1a glottic tumors demonstrated higher laryngectomy rates among early laryngeal cancer patients who required salvage following primary radiation therapy . This is reflected in the 2018 American Society of Clinical Oncology recommendation 1.5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with previous studies. A recent meta‐analysis by Guimaraes et al of eight studies with over 1000 patients with Tis and T1a glottic tumors demonstrated higher laryngectomy rates among early laryngeal cancer patients who required salvage following primary radiation therapy . This is reflected in the 2018 American Society of Clinical Oncology recommendation 1.5 .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we undertook a more focused analysis of LASCC patients. Patients with early stage glottic squamous cell carcinoma (SCC) (T1 and T2 lesions) generally demonstrate excellent treatment response and overall prognosis . Despite the lack of randomized controlled trials, many numerous retrospective studies, systematic reviews, and meta‐analysis have shown relative equivalency between surgery, (open or endoscopic) and external beam radiation therapy (EBRT) .…”
Section: Introductionmentioning
confidence: 99%
“…The disadvantages of radiotherapy include local temporary or persistent edema, glottis stenosis, xerostomia, and hypothyroidism. 9 There is also a small risk of radiation-induced malignancy. The most important factor in laser surgery is to get adequate exposure of the tumor during microlaryngoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…https://www.nice.org.uk/guidance/ng36), with salvage laryngectomy or radiotherapy for recurrence . Rates of local control and 5‐year survival in early‐stage tumours are similar following radiotherapy or TLM (~80%), and meta‐analyses in early glottic cancers suggest improved survival following TLM, with uncertainty regarding vocal quality outcomes . Options for T3/T4 LSCC include radiotherapy, concurrent platinum‐based chemo‐radiotherapy, primary partial or total laryngectomy .…”
Section: Introductionmentioning
confidence: 99%
“…1 Rates of local control and 5-year survival in early-stage tumours are similar following radiotherapy or TLM (~80%), and meta-analyses in early glottic cancers suggest improved survival following TLM, with uncertainty regarding vocal quality outcomes. 3,4 Options for T3/T4 LSCC include radiotherapy, concurrent platinum-based chemo-radiotherapy, primary partial or total laryngectomy. 2,5 Post-radiotherapy recurrence is a major problem, with radiotherapy failure rates of 9%-21% in T1 glottic and 28%-37% in T2 glottic LSCC.…”
mentioning
confidence: 99%